Transformasi Sistem Pendidikan di India: Profil, Tujuan, Manajemen, Pendidikan Islam, dan Tantangan dalam Menghadapi Isu Global - Devi Rosvianto; Mislaini Mislaini; Nila Komala Bintang (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
This research discusses the transformation of the education system in India with a focus on the profile, goals, management, Islamic education and global challenges. The background is India's economic and social development which requires a quality education system. This study aims to analyze the Indian education system and identify the challenges faced. The methods used are literature studies and theoretical analysis with reference to the theory of modernization, inclusion and technology-based learning. The results show that the Indian education system has a structured structure, but still faces educational gaps, uneven quality of education and limited use of technology. Islamic education also faces challenges. This research has implications for the development of the education system in India, especially improving access and quality of education, as well as integrating environmental education in the curriculum. These results can be a reference for the government, educators and researchers to develop a quality education system that is relevant to the needs of society. This research contributes to the understanding of the Indian education system and the development of strategies to improve the quality of education.